"Male athletes play well to feel good, and female athletes feel good to play well": Attitudes, beliefs, and practices pertaining to perceived sex-related differences in communication and interpersonal approach of strength and conditioning coaches in international women`s rugby union - Nolan, D.; Horgan, P.; MacNamara, A.; Egan, B. (Journal of Sports Sciences, 2024)
Effective communication and rapport building with athletes are key tenets of coaching. As the majority of empirical evidence to date has adopted an androcentric view of strength and conditioning, a potential knowledge gap exists regarding sex-related differences in physical preparation and coaching approaches. Therefore, this study explored the attitudes, beliefs and practices of strength and conditioning coaches (n = 8; M/F, 6/2) in elite level (international) women`s rugby union using semi-structured interviews (mean ±standard deviation duration 59 ± 15 min). The interviews explored differences in coaching practices for elite female rugby players compared to males, with a specific focus on the interpersonal aspects of the athlete-coach relationship. Reflexive thematic analysis was used to generate a rich qualitative dataset. The analysis resulted in the identification of higher order themes: athlete engagement, and interpersonal approach. The coaches in this study consistently perceived important differences between male and female players in factors related to engagement and interpersonal approach. Coaches adopted differing coaching practices for male and female athletes. This study provides important contextual evidence for the understanding of differences in the interpersonal relationships of female rugby players compared to male athletes from the perspective of elite-level strength coaches.